Single-branched stent-graft with on-table fenestration for endovascular repair of primary retrograde type A aortic dissection: A multicenter retrospective study - Zhang, Heng; Feng, Jiaxuan; Zhu, Hongqiao; Xiao, Shun; Liu, Mingyuan; Xu, Yili; Yang, Dongshan; Liu, Junjun; Guo, Mingjin (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aims to evaluate the feasibility, efficacy, and safety of a single-branched stent-graft with on-table fenestration for primary retrograde type A aortic dissection (RTAD) during thoracic endovascular aortic repair (TEVAR). Methods: From January 2019 to December 2021, 42 (7.3%) patients with primary RTAD from five tertiary hospitals received medical management during the acute phase. Nearly two weeks after admission, computed tomography angiography (CTA) was re-examined to evaluate the thrombosis status of retrograde false lumen (FL). In the subacute phase, 36 patients (6.2%) underwent TEVAR with a proximal zone 1 landing for aortic arch reconstruction, using a fenestration technique on a single-branched stent-graft. The primary outcomes were technical success, patency of the target branch arteries, and absence of type Ia endoleaks. The second outcomes were stent-graft-related complications and all-cause mortality. Results: The mean age was 56.2 ± 11.3 years, and 29 (80.6%) were male. After a median interval of 18.0 (interquartile range [IQR], 17.0–20.3) days of medical treatment, the partial and complete thrombosis of proximal FL rates increased to 52.8% and 47.2%, respectively. One patient (2.8%) experienced postoperative type Ia endoleaks, and was successfully re-treated using coli and Onyx glue. The median hospital stay was 20.5 (IQR, 18.0–23.0) days. The overall technical success rate was 100%. The median follow-up time was 31.5 (IQR, 29.8–34.0) months. There was one death (2.8%) due to gastrointestinal bleeding. Distal aortic segmental enlargement (DASE) occurred in two (5.6%) patients. No major complications or recurrent dissections in the proximal landing zone were recorded during follow up. Conclusion: The retrograde FL in primary RTAD could realize partial or complete thrombosis after medical management in the acute phase, and it might be regarded as a valid proximal landing zone for endovascular repair. The single-branched stent graft with on-table fenestration performed in the subacute phase may be feasible strategy in selective primary RTAD patients.